Diversity, biological and ecological aspects of marine baitworms, with an emphasis on a polychaete Marphysa moribidii (IDRIS, HUTCHINGS, ARSHAD 2014) from Morib Mangrove area, Malaysia - Idris, Izwandy (2014)
The commercial value of marine baitworms from Class Polychaeta in Malaysia is not fully explored. It was previously researched by selected, local and foreign researchers. Hence, the objectives of the present study are to identify taxonomically polychaete species used as baitworms in Peninsular Malaysia, and to examine the biology and ecology of the dominant species. The study was performed in two phases; the first phase was to systematically identify polychaete species used as baitworms in Peninsular Malaysia. The second phase focused on the biology and ecology of a dominant species from June 2011 to December 2012 at the Morib mangrove area in Selangor, Peninsular Malaysia. Random transect quadrats across three designated tidal flat areas were used to collect samples. A total of seven polychaete species were identified in this study, namely Marphysa moribidii sp. nov., M. cf. sanguinea, Halla okudai, Diopatra claparedii, Namalycastis rhodochorde, N. cf. abiuma and Perinereis cf. nuntia. Marphysa moribidii sp. nov. was named and described in this study while M. cf. sanguinea, N. cf. abiuma and P. cf. nuntia had close similarities with the existing species. All species are new records in Malaysia with the exception of D. claparedii and N. rhodochorde which were previously reported in Kedah and Sabah respectively. Marphysa moribidii sp. nov. is the dominant baitworm species collected by the bait diggers and have a wide distribution across the west coast of Peninsular Malaysia.The population of M. moribidii sp. nov. in Morib mangroves, was mostly confined in the upper tidal flat (UTF) area, particularly within the patchy microhabitat, which was identified as polychaete niche (PN). The microhabitat was characterised by having a high percentage of total organic matter, water content, silt and very fine sand. It was also located around the stilt roots of Rhizophora apiculata, providing protection from potential predators. Allometry analyses indicate that the growth of the species followed an allometric pattern. The maximum life span (tmax) was two years with growth constant (K) of 1.5 year-1. The Bhattacharya and NORMSEP analyses concluded that there were two major spawning events occurred in 2012, although the von Bertalanffy Growth Function (VBGF) was only able to detect one spawning event. The male and female ratio was close to 1:1. The gametogenesis processes were asynchronous in both sexes. Fecundity data revealed that there were two spawning seasons occurred during the study period. Marphysa moribidii sp. nov. exhibited subsurface deposit feeding with high percentage of organic matter found in its intestinal contents. It also practices selective feeding by consuming a higher percentage of very fine sand compared to other sediments size classes. This sediments size class was chosen by M. moribidii sp. nov. for its high surface volume ratio which allowed more surfaces for organic coatings. In summary, several aspects covering the systematics, biology and ecology of marine baitworms, in particular, M. moribidii sp. nov. in Peninsular Malaysia, have been documented in this study. Results obtained indicated that the biology and ecology of M. moribidii sp. nov. in Morib mangrove were interrelated. Moreover, the biological characteristics of M. moribidii sp. nov. meet all the criteria for commercial baitworm species. Nevertheless, more studies are needed to grasp a better understanding of the species, to allow correct resource management and to carefully consider the possibility of rearing the species in an artificial environment.